Coding activities for developing music with Sonic Pi - Small, Cathleen (Code creator (Rosen Publishing Group), 2022)
"Those with an interest in coding and a talent for music can use Sonic Pi, a live coding environment based on the Ruby programming language, to create simple tunes or masterful compositions. This . . . book offers a series of unique activities, starting with live loops and progress to using envelopes and samples, to start readers on a musical coding journey"--Provided by publisher.